Giuseppe Samonà. The Contest of the Second Chamber. The time depth - Alonso García, Eusebio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
Giuseppe Samonà designed in 1967 a project for the contest of the Chamber of Deputies in Rome and managed a lucid synthesis of some of the most important concerns of the architectural debate of the age and employed memorable formal strategies in the way of dealing with the relations between architecture and city and, in particular, its inclusion in the debate on the historical centres which, for Samonà, was a part of a largest debate on the theme of the unity between architecture and planning. We will discuss some of the characteristic mechanisms of Samonà, the idea of the urban continuum versus the problem about the relationship between typology and morphology, the fourth dimension, the free stacking of the different types and the fluffy section, as suitable strategies to take part in the historical center, exploiting the implied creativity in the complex and functional, technical and symbolic reality, and the creation of outdoor shade structures that show through the space and the time depth the inherited image of the historic city in dialogue with a fully modern architecture.
Keywords: Continuous urban; Fourth dimension; Stack types; Outdoor shade structure and transparency